Konferensi Video sebagai Alternatif Media Pembelajaran pada Masa Pandemi Covid-19 - Feni Haryati, Linda; Nursaptini, Nursaptini (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2021)
The Covid-19 pandemic has caused changes in all aspects of life, from the economy, health to education. This situation causes the implementation of learning is usually carried out directly in the classroom, turning into School From Home, students and teachers carry out learning activities from home. These changes of course require adaptation and learning media that are different from previous activities. The purpose of this study is to provide an overview of the use of video conferencing as an alternative medium of learning during the Covid-19 pandemic. The research method used is library research or library research. Library research utilizes library resources to obtain research data. Sources of data obtained from secondary data originating from research reports contained in articles, textbooks, proceedings, and websites as well as other sources deemed relevant to the topic of study. The result of this research study is that video conferencing using Google Meet and Zoom is an alternative learning media that is most widely used by teachers and students in the learning process during the Covid-19 Pandemic. This is because it has several advantages compared to other applications, such as being able to be downloaded for free, students can conduct direct questions and answers like in a face-to-face class. In addition, teachers can also provide feedback. Another advantage is that the teacher can display the material, explain the material as usual in face-to-face learning because there is a whiteboard to explain using handwriting using a pen, recording learning activities, it is easier to control students in following the learning process. Based on these advantages, the use of video conferencing is more dominant in learning activities during the Covid-19 pandemic.